The Effectiveness of The Body of Knowledge Process in The Startup Analysis of Efficiency by Applying Startup Management Body of Knowledge (SUBOK) Guide - Hitoshi, Hirai; Kamei, Shogo; Ohashi, Masakazu (Bright Institute, 2021)
Entrepreneurs who create new businesses using innovative products and services that leverage the basic technologies of the 4th industrial revolution such as AI, IoT, Big Data and others technologies led by Germany and the United States have also emerged in Asia. Due to the diversification of consumer needs in recent years and the need for customer experience management to increase royalties, etc., the development cycle of new products and unique services tends to be shortened and how quickly they can be provided, which is a major problem. success factor. Meanwhile, in order to grow a business sustainably, it is also important to develop the right business strategy, build a governance structure, create value, and raise funds. In this thesis, we consider a startup as a project and describe the usefulness of implementing the Startup Body of Knowledge (SUBOK) Guide which systematizes the process to realize a startup quickly and reliably. In particular, we hypothesize that it is important to balance economic value and social value for startups, and consider the results of the implementation and analysis of the questionnaire.